Cholesterol-lowering therapy evokes time-limited changes in serotonergic transmission - Vevera, Jan; Fišar, Zdenĕk; Kvasnička, Tomáš; Zdeněk, Hanuš; Stárková, Lucie; Češka, Richard; Papežová, Hana (Psychiatry research, 2005)
A number of studies have reported an increased risk for violent deaths and depression in subjects with reduced serum cholesterol concentrations. Links with hypothesized impairment of serotonin neurotransmission have not been satisfactorily tested. In this investigation, the serum and membrane cholesterol, microviscosity of erythrocyte membranes, platelet serotonin uptake, and clinical parameters were determined during pharmacotherapy of 17 hypercholesterolemic patients. A significant decrease in serum cholesterol and a nonsignificant decrease in membrane cholesterol concentration were found after 2 months of simvastatin therapy. Serotonin transporter (SERT) activity was significantly increased following 1 month of simvastatin; the tendency to decrease the initial increase in SERT activity was evident following 2 months of therapy. Both membrane cholesterol and SERT activity returned to pre-treatment levels after more than 1 year of therapy. Microviscosity of plasma membranes, impulsivity, empathy, adventure, sensation seeking, and depressed mood were not markedly changed. These data indicate that long-term therapy has different effects on serotonin transmission from short-term (1- to 2-month) therapy. A significant increase in SERT activity was detected only during the first month of simvastatin therapy. This finding suggests that within this period some patients could be vulnerable to depression, violence, or suicide.